Interplay between Submarine Depositional Processes and Recent Tectonics in the Biak Basin, Western Papua, Eastern Indonesia - Bertoni, Claudia; Álvarez, Juan (Berita Sedimentologi, 2012)
The offshore Biak Basin between Biak and Yapen Islands is a transtensional pull-apart basin. Deposition along basin margins is strongly influenced by active faulting. The bathymetric map of the basin shows submarine depositional processes occurred during relatively recent tectonic activity.